PT⇔√x−1(1+√x+1)=x√x⇔√x−1(1+√x+1)=(√x+1−1)(1+√x+1)√x$\Leftrightarrow \sqrt{x-1}=\sqrt{x}(\sqrt{x-1}-1)$$\Leftrightarrow \sqrt{x-1}+\sqrt{x}=\sqrt{x}\sqrt[]{x-1}$Đặt $\begin{cases}\sqrt{x}=a \\ \sqrt{x-1}=b \end{cases}$Khi dó ta có HPT$\begin{cases}a^2-b^2=1 \\ a+b=ab \end{cases}$Giải hệ ra là ra x;y
PT⇔√x−1(1+√x+1)=x√x⇔√x−1(1+√x+1)=(√x+1−1)(1+√x+1)√x$\Leftrightarrow \sqrt{x-1}=\sqrt{x}(\sqrt{x
+1}-1)$$\Leftrightarrow \sqrt{x-1}+\sqrt{x}=\sqrt{x}\sqrt[]{x
+1}$
Bình phương
lên r
ồi
làm nốt
hộ m nha